NIKAH ONLINE DI MASA PANDEMI COVID-19 DI KUA KECAMATAN MEDAN AMPLAS ANALISIS FIQH HANAFI DAN ASY-SYAFI’I - musliadi (Wahdatul Ulum Institute, 2023)
Abstract This research is comparative normative sociology research. research on online marriage that took place at the KUA Kec. Medan Amplas, Medan City, North Sumatra, The contract process is carried out online with the consent being said by the guardian, the kabul being said by the prospective groom. The issue of marriage as described in fiqh books does not seem to be seen from the type or model of the means used. But more emphasis on whether or not the conditions of marriage can be met. If all the conditions for marriage can be met by both the bride and groom, how the procession is carried out, the marriage is considered valid. And both are bound in a husband and wife relationship. However, if even one condition is not met even though the wedding procession is held in one assembly, the marriage is declared void. If you look at the meaning of